A Single Tim Translocase in the Mitosomes of Giardia intestinalis Illustrates Convergence of Protein Import Machines in Anaerobic Eukaryotes. (28th September 2018) - Pyrihová, Eva; Motyčková, Alžběta; Voleman, Luboš; Wandyszewska, Natalia; Fišer, Radovan; Seydlová, Gabriela; Roger, Andrew; Kolísko, Martin; Doležal, Pavel
Abstract: Mitochondria have evolved diverse forms across eukaryotic diversity in adaptation to anoxia. Mitosomes are the simplest and the least well-studied type of anaerobic mitochondria. Transport of proteins via TIM complexes, composed of three proteins of the Tim17 protein family (Tim17/22/23), is one of the key unifying aspects of mitochondria and mitochondria-derived organelles. However, multiple experimental and bioinformatic attempts have so far failed to identify the nature of TIM in mitosomes of the anaerobic metamonad protist, Giardia intestinalis, one of the few experimental models for mitosome biology. Here, we present the identification of a single G. intestinalis Tim17 protein (GiTim17), made possible only by the implementation of a metamonad-specific hidden Markov model. While very divergent in primary sequence and in predicted membrane topology, experimental data suggest that GiTim17 is an inner membrane mitosomal protein, forming a disulphide-linked dimer. We suggest that the peculiar GiTim17 sequence reflects adaptation to the unusual, detergent resistant, inner mitosomal membrane. Specific pull-down experiments indicate interaction of GiTim17 with mitosomal Tim44, the tethering component of the import motor complex. Analysis of TIM complexes across eukaryote diversity suggests that a "single Tim" translocase is a convergent adaptation of mitosomes in anaerobic protists, with Tim22 and Tim17 (but not Tim23), providing the protein backbone.